Composite Encapsulating Agent for NaFeEDTA Microencapsulation Using Spray Drying Method - Handayani, Noer Abyor; Aryanti, Nita; Haryani, Kristinah; Hargono, Hargono; Adina, Alifia Rizki; Yuliani, Sari; Adristy, Vania Zulfa (Department of Chemical Engineering, Faculty of Engineering, Universitas Diponegoro, 2025)
Iron microencapsulation is one of the solutions to protect iron from reacting with other substances that result in quality declines of fortified food products. The coating materials used should be appropriate for the specified encapsulation process. This study combined glucomannan and maltodextrin as coating materials and added HPMC as an additive to encapsulate NaFeEDTA. The results showed that such a combination could increase the encapsulation efficiency. The morphologies of the resulting microcapsules obtained from four formulations applied in this study were identical; numerous wrinkles appear on the particle’s surfaces due to the presence of HPMC. All formulations had a narrow size distribution with an average particle size between 105 and 111 µm, thermal resistance up to a temperature of ± 200°C, and the same functional groups but with different intensities. The NaFeEDTA included in all formulations had a bioavailability value of 2.3 - 2.9%. The best formulation, based on the gastrointestinal digestion simulation, was shown by the formulation with a glucomannan:maltodextrin ratio of 2:3 (in 1% w/v coating material) with a release percentage of 64.28% in SGF solution and an increase of 2.27% in SIF solution. To prevent anemia, ± 400 mg of iron microcapsules resulting from the best formulation in this study are required to meet 75% of the daily intake.